Angelica purpurascens (Ave-Lall.) Gilli. Essential Oil Improved Brain Function via Cholinergic Modulation and Antioxidant Effects in the Scopolamine-Induced Zebrafish (Danio rerio) Model - Boiangiu, Razvan Stefan; Bagci, Eyup; Dumitru, Gabriela; Hritcu, Lucian; Todirascu-Ciornea, Elena (Mdpi, 2022)
Angelica purpurascens (Ave-Lall.) Gilli. is a medicinal plant that displays antioxidant, anticholinesterase, and neuroprotective properties. The effect of A. purpurascens essential oil (APO) on memory impairments and brain oxidative stress in zebrafish (Danio rerio) treated with scopolamine (Sco), as well as the underlying mechanism involved, were investigated in this study. Exposure to Sco (100 mu M) resulted in anxiety in zebrafish, as assessed by the novel tank diving test (NTT), whereas spatial memory and novelty response dysfunctions, as evidenced by the Y-maze test and novel object recognition test (NOR), were noticed. When zebrafish were given Sco and simultaneously given APO (25 and 150 mu L/L, once daily for 13 days), the deficits were averted. An increase in brain antioxidant enzymes, a reduction of lipid peroxidation, and protein oxidation were linked to this impact. Furthermore, acetylcholinesterase (AChE) activity was significantly reduced in the brains of APO-treated zebrafish. The main detected components in the APO composition were beta-phellandrene (33.80%), sabinene (6.80%), alpha-pinene (5.30%), germacrene-D (4.50%), alpha-phellandrene (4.20%), and p-cymene (3.80%) based on gas chromatography-mass spectrometry (GC-MS) investigations. Our findings show that APO's beneficial effect in a zebrafish model of Sco-induced memory impairment is mediated through multiple mechanisms, including the restoration of cholinergic system function and the improvement of the brain antioxidant state. As a result, APO could be employed as a potential source of bioactive molecules with useful biological properties and medicinal uses.
Keywords: Angelica purpurascens; scopolamine; acetylcholinesterase; oxidative damage; memory